Genética poblacional de cobayas de Colombia, Cavia spp. (Rodentia: Caviidae) con marcadores moleculares RAPD - Aníbal Campos, Héctor; Ruiz García, Manuel (Revista de Biología Tropical, 2008)
The genus Cavia occurs in South America, mainly in grasslands.. We collected blood samples from 97 individuals in six field populations and analyzed them with RAPD molecular markers. One wild type (C. anolaimae) was differentiated from the domestic form (C. porcellus), in agreement with other authors who used morphological, osteological and karyotipic results. Genetic diversity was considerable in both species, but higher in C. porcellus. The levels of genetic heterogeneity were also higher among the populations of C. porcellus (FST = 0.254) than among the populations of C. anolaimae (FST = 0.118). These significant levels of genetic heterogeneity, and the low levels of gene flow, were consistent with a complex domestication process for Cavia porcellus.